Home | | Maths 10th Std | Least Common Multiple (LCM) of Polynomials

Least Common Multiple (LCM) of Polynomials - Example, Solution | Algebra | Study Material, Lecturing Notes, Assignment, Reference, Wiki description explanation, brief detail |

Chapter: 10th Mathematics : Algebra

Least Common Multiple (LCM) of Polynomials

The Least Common Multiple of two or more algebraic expressions is the expression of lowest degree (or power) such that the expressions exactly divide it.

Least Common Multiple (LCM) of Polynomials

The Least Common Multiple of two or more algebraic expressions is the expression of lowest degree (or power) such that the expressions exactly divide it.

Consider the following simple expressions a3b2a2b3 .

For these expressions LCM = a3b3.

To find LCM by factorization method

(i) Each expression is first resolved into its factors.

(ii) The highest power of the factors will be the LCM.

(iii) If the expressions have numerical coefficients, find their LCM.

(iv) The product of the LCM of factors and coefficient is the required LCM.

 

Example 3.12

Find the LCM of the following

(i) 8x4y2, 48x2y4

(ii) 5x -10, 5x2 – 20

(iii) x 4  -1, x 2 − 2x + 1

(iv) x 3 - 27, (x - 3)2, x 2 – 9

Solution

(i) 8x 4y2, 48x 2y4

First let us find the LCM of the numerical coefficients.

That is,      LCM (8, 48)  = 2 × 2 × 2 ×6 = 48

Then find the LCM of the terms involving variables.

That is, LCM (x 4y2, x 2y4 )  = x 4y4

Finally find the LCM of the given expression.

We condclude that the LCM of the given expression is the product of the LCM of the numerical coefficient and the LCM of the terms with variables.

Therefore, LCM (8x 4y2, 48x 2y4 ) = 48x 4y4

(ii) (5x -10), (5x 2 - 20)

5x -10 = 5(x − 2)

5x 2 - 20 = 5(x 2 − 4) = 5(x + 2)(x − 2)

Therefore, LCM [(5x − 10),(5x 2 −20)] = 5(x + 2)(x −2)

(iii) (x 4  -1),  x 2 − 2x + 1

x4 -1  = (x 2 )2 −1 = (x 2  + 1)(x 2 −1) = (x 2  + 1)(x + 1)(x −1)

x 2 2x + 1 = (x −1)2

Therefore, LCM [(x 4 − 1),(x 2 −2x +1)] = (x 2  + 1)(x + 1)(x −1)2

(iv) x 3 - 27, (x - 3)2, x 2 9

x 3 - 27 = (x 3)(x 2  + 3x + 9) ; (x − 3)2  = (x − 3)2 ; (x 2 − 9) = (x + 3)(x − 3)

Therefore, LCM [(x 3 - 27),(x - 3)2,(x 2 - 9)] = (x − 3)2 (x + 3)(x 2  + 3x + 9)


Tags : Example, Solution | Algebra Example, Solution | Algebra
Study Material, Lecturing Notes, Assignment, Reference, Wiki description explanation, brief detail


Copyright © 2018-2021 BrainKart.com; All Rights Reserved. (BS) Developed by Therithal info, Chennai.